P-B2 HIV envelope gp120 fused to IgG1 Fc fragment exhibits augmented immunogenicity compared to unmodified immunogen and elicits a neutralizing antibody response in rhesus macaques. (March 2017) - Shubin, Zhanna; Li, Weizhong; Labranche, Celia; Montefiori, David; Zhu, Xiaoping; Pauza, David
Abstract : A major focus of HIV prevention programs is the development of a safe and effective vaccine. A successful vaccine will elicit broadly neutralizing antibodies (bNAb) with high durability and protect against both sexual and blood-borne HIV transmission. Most neutralizing antibodies target critical epitopes on the surface, or gp120, portion of HIV envelope glycoprotein (Env). We developed a new immunogen by engineering a fusion protein containing HIV gp120 (BaL strain) with a Gly/Ser linker fused to each arm of the Fc domain of rhesus macaque IgG1 (Env-rFc). We envisioned that Env-rFc, which mimics the behavior of immune complexes, would bind to Fc gamma receptors on antigen-presenting cells to increase the strength, breadth and durability of Env-specific antibody responses. The Env portion retained structure and function, as it was capable of binding to cell surface CD4. The Fc portion was also functional, demonstrating direct binding to Fc gamma receptor followed by rapid cell uptake and accumulation in cytoplasmic vesicles. We then conducted an immunization study in rhesus macaques, comparing Env-rFc and Env (gp120 monomer) delivered by the intramuscular route. Overall, Env-rFc proved superior to Env monomer. Env-rFc elicited higher titer antibodies with increased breadth capable of recognizing CD4-induced epitopes. Env-rFc also elicited antibodies capable of neutralizing Tier1 HIV pseudotyped viruses and the serum antibodies were more durable compared to serum IgG responses seen with Env monomer immunization. The clear differences between Env monomer and Env-rFc indicate a strong advantage of the fusion protein strategy that may be improved by dose and adjuvant optimization.